The French Great Depression: A business cycle accounting analysis - Slim Bridji (University of Zurich, Department of Economics, 2012)
Using the business cycle accounting framework [Chari V., P. Kehoe and E. McGrattan 2007. Business Cycle Accounting. Econometrica 75, 781-836.], this paper sheds new light on the French Great Depression. Frictions that reduce the efficiency with which factor inputs are used (efficiency wedge) were the primary factor in the economic downturn. The decline in consumption can be attributed to distortions in the Euler equation (investment wedge). In addition, frictions creating a gap between the marginal rate of substitution and the marginal product of labor (labor wedge) contributed to the slowdown of the economy after 1936. This drop in the efficiency wedge might have resulted from financial frictions and tariff policies, whereas the investment wedge might have been caused by financial frictions due to agency costs. A potential explanation for the decline of the labor wedge after 1936 is institutionals changes in the labor market.
Keywords: E32; N14; N44; 330; Business Cycle Accounting; French Economy; Great Depression; Konjunktur; Kapazitätsauslastung; Theorie; Frankreich